TOPICS IN MEDICAL EDUCATION ELECTIVE BLOCK: A STUDY USING DELPHI METHOD - Geraldo Geraldo; Elisabeth Rukmini (Jurnal Pendidikan Kedokteran Indonesia, 2019)
Background: Problematic practices performed by doctors and clinical phase students often be found in the workplace settings. Common problems related to team working is the highest rated problems. To overcome this problem, we designed an elective course, Medical Education block (ME) and have implemented the course since 2014. This study aimed to find topics in ME which were meaningful toward medical student’s practices.